2011
DOI: 10.1007/978-1-61779-501-5_37
|View full text |Cite
|
Sign up to set email alerts
|

Karyotyping Methods for Fungi

Abstract: Pulsed field gel electrophoresis enables separation of fungal chromosomes up to several megabases and is a worthwhile tool for fungal karyotyping. The germ tube burst method is a technique to separate fungal chromosomes of any size for chromosome number determination as well as in situ hybridization. Here we provide detailed protocols for both complementary methods that have many applications in fungal biology including chromosome size and chromosome number polymorphisms, and in situ localization of genes on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In order to comprehensively identify genetic components related to sclerotium formation, we sequenced a cultivated strain of W. cocos 2018LT001 (sampled in Luotian, Hubei, China; named WCLT hereafter). We first determined the chromosome number of this strain using the germ burst method ( Mehrabi et al, 2012 ), which clearly showed 14 chromosomes of diploid WCLT under microscopy ( Supplementary Figure 1 ). After sequencing by Illumina and PacBio platforms, we estimated the WCLT genome size to be 62 Mb (in haploid) using 31-nt k-mers ( Marçais and Kingsford, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to comprehensively identify genetic components related to sclerotium formation, we sequenced a cultivated strain of W. cocos 2018LT001 (sampled in Luotian, Hubei, China; named WCLT hereafter). We first determined the chromosome number of this strain using the germ burst method ( Mehrabi et al, 2012 ), which clearly showed 14 chromosomes of diploid WCLT under microscopy ( Supplementary Figure 1 ). After sequencing by Illumina and PacBio platforms, we estimated the WCLT genome size to be 62 Mb (in haploid) using 31-nt k-mers ( Marçais and Kingsford, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…We performed Illumina and PacBio platform sequencing, together with Hi-C-assisted assembly for a cultivated strain of W. cocos PCmonoA, to draft a chromosomal-level genome. Prior to sequencing, we were able to observe the W. cocos chromosome numbers under light and fluorescent microscopy by a germ bust method ( Mehrabi et al, 2012 ). The 14 chromosomes from microscopy were consistent with the sequence assembly of the diploid W. cocos .…”
Section: Discussionmentioning
confidence: 99%
“…dahliae mycelium was prepared for protoplasting following the mycelium-based fungal biomass preparation method (Mehrabi et al 2012). Mycelium was digested in 1 M sorbitol containing 1% (w/v) glucanex and 0.5% driselase (Sigma-Aldrich) at 32°C until protoplast concentration reached 10 8 /mL.…”
Section: Karyotypingmentioning
confidence: 99%
“…Mycelium was digested in 1 M sorbitol containing 1% (w/v) glucanex and 0.5% driselase (Sigma-Aldrich) at 32°C until protoplast concentration reached 10 8 /mL. Protoplast plugs were prepared and stored as described (Mehrabi et al 2012). Karyotyping was carried out using a CHEF Mapper XA pulsed field electrophoresis system (Bio-Rad) using the auto algorithm function with low-and high-molecular weight settings at 2 and 6 Mb, respectively.…”
Section: Karyotypingmentioning
confidence: 99%
“…Strains were maintained as slant cultures using synthetic low nutrient agar (SNA, Nirenberg 1976 ), vegetable juice agar [10 % (v /v) mix vegetable juice (Kagome, Nagoya, Japan), 0.3 % (w /v) CaCO3, 1.5 % (w/v) agar] or potato dextrose agar (Difco, Detroit, Michigan). The germ tube burst method (GTBM) was used to prepare microscope slides containing mitotic metaphase chromosomes as previously described ( Taga et al , 1998 , Tsuchiya & Taga 2010 , Mehrabi et al 2012 ). To obtain macroconidia for the GTBM, fusaria were cultured on SNA containing small pieces of filter paper ( Aoki & O’Donnell 1999 ), carnation leaf agar (CLA) ( Nelson et al 1983 ) or mung bean broth (MBB, Gale et al 2005 ).…”
Section: Methodsmentioning
confidence: 99%